Marxist modern an ethnographic history of the Ethiopian revolution - Donham, Donald L. (Berkeley University of California Press, 1999)
Modernity has become a keyword in a number of recent intellectual discussions. In this book, Donald L. Donham shows that similar debates have long occurred, particularly among peoples located on the margins of world power and wealth. Based on extensive fieldwork in Ethiopia?conducted over a twenty-year period?Marxist Modern provides a cultural history of the Ethiopian revolution that highlights the role of modernist ideas.
Includes bibliographical references (p. 217-228) and index.
Keywords: Communism--Ethiopia--Gamo Gofa Kifle Hāger--History--20th century